2019
DOI: 10.1159/000499322
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Multiparametric MRI May Augment the Response to Radiotherapy in Mid-Treatment Assessment of Patients with Esophageal Carcinoma

Abstract: Objective: The purpose of this study was to assess the mid-treatment response to radiotherapy (RT) using dynamic contrast-enhanced MRI (DCE-MRI) and diffusion-weighted imaging (DWI) in patients with esophageal cancer (EC). Methods: 42 patients with squamous EC were prepared for DCE-MRI and DWI scans both before treatment (NRT) and after the fifth radiotherapy (5th RT). The patients were classified into two groups (complete response [CR] and partial response [PR]) according to tumor regression after treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…220 In another study using both DCE-MRI and DWI, K trans and k ep acquired in the middle of the RT course captured significant differences between different responsive groups, but ADC only indicated such difference in pretreatment results. 221 Another study reported that a90% percentile change in CA concentration AUC could predict pathologic complete response after neoadjuvant chemo-RT. 222 In a T1 mapping study assessing cardiac toxicity after esophagus chemo-RT, pre-CA T1 value of myocardium increased 6 months after treatment, which was earlier than late CA enhancement results that demonstrated significant results 18 months after treatment.…”
Section: May Indicates a Statement That Is Likely (Or Probably)mentioning
confidence: 99%
See 1 more Smart Citation
“…220 In another study using both DCE-MRI and DWI, K trans and k ep acquired in the middle of the RT course captured significant differences between different responsive groups, but ADC only indicated such difference in pretreatment results. 221 Another study reported that a90% percentile change in CA concentration AUC could predict pathologic complete response after neoadjuvant chemo-RT. 222 In a T1 mapping study assessing cardiac toxicity after esophagus chemo-RT, pre-CA T1 value of myocardium increased 6 months after treatment, which was earlier than late CA enhancement results that demonstrated significant results 18 months after treatment.…”
Section: May Indicates a Statement That Is Likely (Or Probably)mentioning
confidence: 99%
“…In a study of esophageal squamous cell carcinoma (SCC) chemo‐RT, DWI ADC was used to identify significant survival rate difference 220 . In another study using both DCE‐MRI and DWI, K trans and k ep acquired in the middle of the RT course captured significant differences between different responsive groups, but ADC only indicated such difference in pre‐treatment results 221 . Another study reported that a90% percentile change in CA concentration AUC could predict pathologic complete response after neoadjuvant chemo‐RT 222 .…”
Section: Mpmri In Rt Treatment Response Assessmentmentioning
confidence: 99%
“…A common way to measure perfusion is by using dynamic contrast enhanced (DCE-) MRI ( 2 , 4 , 5 ). In addition to prognosis, DCE has been shown to have value for mid-treatment response assessment in cervix ( 6 ), esophageal ( 7 ), and head-and-neck cancer ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…DCE-MRI parameters can also reflect tumor angiogenesis and, therefore, provide essential information about the prognosis and effect of treatment for LARC (17). Moreover, in various oncology fields, several researchers have recommended using DCE-MRI to assess response to radiotherapy (18,19). Li et al (20) showed that radiomics features based on breast DCE-MRI could identify the status of some pathological markers (HER2 and Ki-67).…”
Section: Introductionmentioning
confidence: 99%